The influence of intercritical heat treatment on the temper embrittlement susceptibility of aP-Doped Ni-Cr steel - Ücisik, A. H.; Mcmahon, C. J.; Feng, H. C. (Springer Science and Business Media LLC, 1978)
Temper embrittlement of a Ni-Cr steel doped with 0.06 wt pct P aged at 480°C after an intercritical heat treatment (IHT) has been compared with that of the conventionally heat treated steel with a range of prior austenite grain sizes. The IHT virtually eliminated the embrittlement susceptibility, but low temperature brittle fracture was still intergranular. It appears that most of the benefit of IHT in this steel comes from microstructural refinement; however, IHT also reduced the amount of segregation of Ni and P to grain boundaries. This is believed to be connected with partitioning of Cr during IHT.